Integrating Digital Technology and Science Learning to Enhance 21st-Century Competencies among Primary School Teacher Education Students - Santhi Pertiwi; Gia Pratiwi Mardianty; Sri Nurafifah; Sugi Aliwibowo (Jurnal Review Pendidikan Dasar : Jurnal Kajian Pendidikan dan Hasil Penelitian, 2026)
The fast growth of digital technology has changed how education is done, including how science is taught in college. Future teachers who want to work in elementary schools need to have skills that are important in the 21st century. These skills include thinking critically, being creative, working together with others, communicating effectively, and being able to use digital tools. This study looks at how using digital technology in science lessons can help improve 21st-century skills for students studying to become primary school teachers. The study used a literature review approach by looking at important national and international articles about digital learning, science teaching, and skills needed in the 21st century. The results show that using digital tools in science classes helps students become more involved, better understand science, improve their ability to solve problems, and work better together in groups. Digital tools like learning management systems, interactive multimedia, virtual labs, and educational apps offer valuable learning experiences and help students develop stronger thinking skills. Using digital technology along with science education is a good way to help future elementary school teachers get ready for the challenges of teaching in the modern digital age.